The investigation of job stress and job satisfaction among workers and its relation to individual factors and non-fatal injuries - Abedi Kamal; Mohsen Zare; Barkhordari Abolfazl; Halvani Gholam Hossein (فصلنامه دانشگاه علوم پزشکی جهرم, 2009)
Introduction: the study of job stress and dissatisfaction among people could cause to identify the reason of problems in workplaces. The objective of this study was to measure the work stress and job dissatisfaction between employees of a industry, and determine its relationship with accidents and individual factors.